1996
DOI: 10.1021/jo951767q
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of cis-Trikentrin B

Abstract: Natural cis-trikentrin B was synthesized enantioselectively using, as key steps, an intramolecular Diels-Alder reaction of an allenic dienamide followed by aromatization to construct an indole ring and cleavage of bicyclo[2.2.1]heptene to launch a cis-dimethylcyclopentane ring. Diels-Alder adducts 9 and 10 were elaborated to provide allenic dienamide 25, and its intramolecular Diels-Alder reaction proceeded smoothly. Aromatization to an indole ring and stereoselective cleavage of the bicyclo[2.2.1]heptene ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Since nonctivated alkynes are poor dienophiles in DielsAlder cycloadditions, [10] the variety of 2,3-disubstituted norbornadienes which could be synthesized using the Diels-Alder method is rather limited (they usually contain at least one electronic withdrawing group such as an ester, an amide or a cyano group etc). We have recently reported the synthesis of a variety of 2,3-disubstituted norbornadienes by a double lithium-halide exchange of 2,3-dibromonorbor-In our case, we found that among various phosphane ligands tested, only tBu 3 P provided good yields in the coupling reactions between 2,3-dibromonorbornadiene 2 and 4-ethylphenylboronic acid 8b (entries [1][2][3][4][5][6][7][8]. In the presence of [Pd 2 (dba) 3 ] (0.5 mol%), a monodentate phosphane (1.4 mol%; Ph 3 P, Cy 3 P, nBu 3 P, (2-furyl) 3 P or TTMPP, entries 1-4, 6) or phosphite (1.4 mol%, entry 5) or a bidentate phosphane (entry 7) and CsF (6.6 equiv.)…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Since nonctivated alkynes are poor dienophiles in DielsAlder cycloadditions, [10] the variety of 2,3-disubstituted norbornadienes which could be synthesized using the Diels-Alder method is rather limited (they usually contain at least one electronic withdrawing group such as an ester, an amide or a cyano group etc). We have recently reported the synthesis of a variety of 2,3-disubstituted norbornadienes by a double lithium-halide exchange of 2,3-dibromonorbor-In our case, we found that among various phosphane ligands tested, only tBu 3 P provided good yields in the coupling reactions between 2,3-dibromonorbornadiene 2 and 4-ethylphenylboronic acid 8b (entries [1][2][3][4][5][6][7][8]. In the presence of [Pd 2 (dba) 3 ] (0.5 mol%), a monodentate phosphane (1.4 mol%; Ph 3 P, Cy 3 P, nBu 3 P, (2-furyl) 3 P or TTMPP, entries 1-4, 6) or phosphite (1.4 mol%, entry 5) or a bidentate phosphane (entry 7) and CsF (6.6 equiv.)…”
Section: Introductionmentioning
confidence: 75%
“…2,3-Disubstituted norbornadienes are important compounds which have found a place as key intermediates in the synthesis of many natural products such as the prostaglandin endoperoxides PGH 2 and PGG 2 , [1] cis-Trikentrin B [2] and β-santalol.…”
Section: Introductionmentioning
confidence: 99%
“…Various cycloalkyl magnesium halides underwent the reaction, giving the corresponding cross-coupling products in moderate to good yields (50-81%, entries [1][2][3][4][5]. This iron-catalyzed coupling reaction of triflate 20 not only worked well with cycloalkyl Grignard reagents, it also worked well with acyclic primary, secondary and even tertiary-alkyl groups (entries 6-9), giving the anti-2,7-disubstituted norbornadienes with R = i-Pr, n-Bu, s-Bu, t-Bu groups in good yields (50-75%).…”
Section: Scheme 4 Synthesis Of Anti-tert-butoxynorbornadien-2-yl Trifmentioning
confidence: 99%
“…Substituted norbornadienes are important compounds. They have been used as key intermediates for the synthesis of natural products such as prostaglandin endoperoxides PGH 2 and PGG 2 , 4 cis-Trikentrin B, 5 and b-santalol. 6 Chiral 2,5-disubstituted norbornadienes 5 have recently been used as chiral ligands in asymmetric catalysis.…”
mentioning
confidence: 99%
“…Ano, Autor, Detalhamento 28 ; assimétrica (não natural); 9 etapas indolização de pirróis Obtida juntamente com o isômero trans [c] 1990: Natsume 30 ; racêmica; 6 etapas indolização de pirróis Obtida juntamente com o isômero trans [c] 1991: Boger 46 ; racêmica; 7 etapas hetero-Diels-Alder Boa seletividade na formação do 1,3-dimetilciclopentano 1994: Natsume 27 ; assimétrica (natural); 17 etapas indolização de pirróis Obtida juntamente com o isômero trans [c] 1995: Blechert 35 [c] 1996: Kanematsu 31 ; assimétrica; 30 etapas Diels-Alder intramolecular Obtida com o isômero trans [c] 2005 Excelente rendimento e excesso enantiomérico na etapa assimétrica 1989: Natsume ; assimétrica (não natural); 9 etapas indolização de pirróis Obtida com o isômero cis [c] 1990: MacLeod 23 ; racêmica; 11 etapas ciclização radicalar Baixa seletividade na formação do 1,3-dimetilciclopentano 1990: Natsume 30 ; racêmica; 6 etapas indolização de pirróis Obtida com o isômero cis [c] 1991: Boger 46 ; racêmica; 8 etapas hetero-Diels-Alder Baixa seletividade na formação do 1,3-dimetilciclopentano 2008: Silva 40 ; racêmica (diastereosseletiva); 20 etapas contração de anel Sem necessidade de separação dos diasteros cis/trans 2012: Silva 41 ; assimétrica; 20 etapas contração de anel e resolução enzimática 1990: Natsume 30 ; racêmica; 7 etapas indolização de pirróis Obtida juntamente com o isômero cis [c] 1993: Natsume 29 ; assimétrica (não natural); etapas indolização de pirróis Obtida juntamente com o isômero cis [c] 1990: Natsume 30 ; racêmica; 6 etapas indolização de pirróis Baixo rendimento global (< 1%).…”
Section: Moléculaunclassified